THE ROLE OF CUSTOMER INNOVATION AND ORIENTATION ON THE BUSINESS PERFORMANCE OF PT PEGADAIAN (PERSERO) SUMATERA AREA OF SOUTH SECTION - Prasetyo, Joko; Syamsurijal AK; Zakaria Wahab; Muchsin Saggaff Shihab (Dinasti Publisher, 2020)
Facing increasingly stringent global markets, PT Pegadaian (Persero) continues to innovate various products and services, but its business performance has not yet satisfied various parties. The purpose of this study is to determine the role of innovation in the relationship between customer orientation and business performance. Another objective is to obtain empirical evidence of the influence of customer orientation both directly and indirectly on the business performance of PT Pegadaian (Persero). The design of this study uses a quantitative approach with a survey method. The research model is confirmatory, so the data analysis technique used is the structural equation model (SEM) with the application of the LISREL program. The study population was all customers of PT. Pegadaian (Persero) in the Southern Sumatra Region. The total sample of 120 respondents taken by accidental sampling. The results of this study indicate that the direct influence of customer orientation on business performance is smaller than the indirect effect. This shows that the innovation variable is a good mediator for the relationship between customer orientation and business performance. The better customer orientation is done, it will increase innovation, which in turn will affect the business performance of PT Pegadaian (Persero). The managerial implication of this research is the need for PT Pegadaian, especially in the marketing division to continue to carry out customer-oriented marketing strategies with various innovations that customers need.